Building Students' Religious Character Through Project-Based Islamic Religious Education Learning in the Independent Curriculum Era - Risza Presty Rumani (PT. Anagata Sembagi Education, 2026)
This study aims to explore the formation of students' religious character through project-based Islamic Religious Education (PAI) learning in the Merdeka Curriculum era. Using a qualitative, descriptive-analytical approach, the study was conducted in several junior high schools in Bandung City with research subjects including PAI teachers, students, and principals. Data collection techniques used triangulation methods in the form of participant observation, in-depth interviews, and documentation studies. The results of the study indicate that project-based PAI learning is able to shape students' religious character effectively through the internalization of Islamic values ​​in real activities. Designed projects such as digital campaigns on honesty, educational videos on tolerance, and social activities based on Islamic values ​​have been proven to improve the understanding and application of religious teachings in everyday life. The implementation of Project-Based Learning (PJBL) provides space for students to experience a meaningful, collaborative, and reflective learning process. However, there are challenges in implementation such as limited resources, teacher readiness, and evaluation complexity. This study recommends the development of an adaptive curriculum and a continuous training program for teachers to optimize the effectiveness of project-based PAI learning in shaping students' religious character that is holistic, moderate, and inclusive in accordance with the spirit of the Merdeka Curriculum